Anlysis Of Factors Affecting Price Movements Of The Joint Stock Index On Indonesia Stock Exchange In 2015-2019 - Jonerli Gunawan; Ella Silvana Ginting (Junal Ilmu Manajemen, 2021)
The study aims in determining and analyzing the effect ofInflation Rate, Exchange rate, Interest rate and Oil Prices on Indonesia Composite Index simultaneously and partially on the Indonesian Stock Exchange in 2015-2019. The population that is used in this study is Indonesia Composite Index on the Indonesian Stock Exchange (IDX) period in 2015 to 2019 which totaling 60 months. The samplex selection uses a saturated sampling technique so all polulation are used as samples. This research used quantitative descriptive by testing classic assumption tests and multiple linear regression analysis using IBM SPSS Statistics 21 aplications.Simultaneously Inflation Rate, Exchange rate, Interest rate and oil price have an effect on Indonesia Composite Index. Partially, Infaltion Rate and Oil Price have a significant effect on Indonesia Composite Index while Exchange Rate, Interest Rate have no effect on Indonesia Composite Index in Indonesia Stock Exchange Periode 2015-2019.